Intervenções urbanas e dinâmica local: o processo de requalificação do centro histórico de Gênova, Itália - Gagliardi, Clarissa Maria Rosa (2011)
The redesign policies of urban spaces have been seen as instruments to suit cities to the demands of capital for new spaces of reproduction and often such transformations overlap the aspirations of the place itself. The historical centers, favorable zones for such policies for their cultural potential to generate new economical opportunities, end up being a point of convergence between dimensions of local life and distant interests. But on account of the peculiarity how each experience is built, according to the different levels of participation of the social groups involved, the historical inheritance of each town, the political usages proper to each administration, in sum, having the local culture as mediator, it is possible to notice that urban redesign plans may not respond exclusively to market interests, but they can also attend society local necessities, gathering distant and proximate orders. Therefore, it is assumed that there are no predefined models of urban redesign plans, unless as the result of social activity at a certain time and in a certain space, which makes important to know each of the cases in which this kind of policy is introduced. Here the analysis is centered on two recent redesign programs of the historical center of the Italian city of Genoa, the Program URBAN II, an initiative of the European Community, and the Contratto di Quartiere del Ghetto, promoted by the Italian Ministry for Infrastructure and by the Region of Liguria. Based on an approach of qualitative countenance and driving attention to the local context and to the typology of the interventions that distinguish the programs, this thesis tries to identify the relevance of social activity of the various participants on the process and of local inheritance, reflecting upon the implication that this kind of policy has on the city, its impact on urban space and the new uses it induces in the areas where it occurs